(untitled) (The Peerian Journal, 2023)
Interest in researching the issue of psychological competence of specialists has become much more intense in later times. The diversity of views and opinions on this issue does not allow us to create a systematized, unified conceptual model for the time being. Of course, the understanding of psychological competence is determined by the parsing of various manifestations of personality activity. The main focus of the article is on the issue of the development of professional competence of the teacher, reflecting on the psychological factors of the development of professional competence in the listeners of educational institutions specializing in retraining and professional development.